Pengaruh Premi, Hasil Underwriting dan RBC terhadap ROA pada Asuransi Syariah yang Terdaftar di OJK Periode 2016-2020 - Tresnawati Tresnawati; Yudhy Yudhy; Nur'aeni Nur'aeni (Ma'soem University, 2022)
This study aims to determine how the influence of premiums, underwriting results, and RBC (Risk Based Capital) on ROA (Return on Assets) in Sharia General Insurance Registered at OJK (Financial Services Authority) either partially or simultaneously. This research method is associative quantitative with secondary data type in the form of sharia general insurance financial reports published by OJK from 2016 to 2020. The data collection techniques include documentation and literature study. While the data analysis used is multiple correlation analysis, multiple regression analysis, coefficient of determination analysis, t test design, and F test design. The results show that there is no influence between premiums on ROA in sharia general insurance registered with the OJK, there is a positive and negative effect. There is a significant relationship between underwriting results on ROA on sharia general insurance registered with the OJK, and there is no effect between RBC on ROA on sharia general insurance registered with the OJK.